Managing waiting time in health care organization: A case study of Emergency Department (ED) in Hospital Raja Perempuan Zainab II (HRPZ II), Kelantan - Lee, Joeanne Li Shi (2023)
Hospital Raja Perempuan Zainab II (HRPZ II) is a government hospital that can be found in Kota Bharu, which is located in the state of Kelantan, Malaysia. It is the largest hospital in the state of Kelantan. In Malaysia, there are many government hospitals located in different states which providing the health care services to patients. This case study focuses on the Emergency Department (ED) in HRPZ II. The experience of outpatients waiting in the ED is the focus of the study. Objective of this case study is to determine the relationship between the communication of delays, overcrowding of patients, and timing of patients’ arrival towards the management of waiting in ED, as well as the aim of the solutions to be executed to solve this issue. The problem of managing waiting time is continuous arising stated that the main key of the waiting time management is overcrowding in HRPZ II Emergency Departments. There are several challenges in managing the waiting time ED which is including that hospital in Malaysia is facing the services insufficient provision to meet the high demand. ED in HRPZ II facing the issues when the patients are not providing the accurate details and information to the staff which leading to the Inconvenient of the management. Waiting time in ED also leads to the worsening the timing of the outpatient to consult with the doctor about their disease. Emergency Department are challenged to provide an effective healthcare. This case study details a number of measurements made to fix internal problems and improve operations of ED in HRPZ II, such as reducing the discrepancy between capacity and demand, applying lean management, enhancing the number of procedures and so on. However, the patients and hospital must works together to achieve the optimum results. A further positive step in the right direction is the need that the problem to be tackled.